Partial discharge characteristics of surface tracking on oil-impregnated pressboard under AC voltages - Zainuddin, Hidayat; Lewin, P. L.; Mitchinson, P. M. (2013)
Creeping discharge at the oil-pressboard interface is a serious fault condition because it can lead to catastrophic failure under normal operating conditions of large transformers. Creeping discharge leads to the development of a conducting path that is generally accepted as white marks on a board surface due to localised heating. The visible white marks indicate a drying out process of the pressboard through moisture evaporation and the breaking of oil molecules to generate gases in the pressboard pores. The processes can continue from minutes to months or even years until failure. Characterising this type of faulty condition in a condition monitoring programme is important for transformer life management. This paper explains the behaviour of surface discharge observed during a surface discharge experiment at the oil-pressboard interface using a needle-bar electrode configuration. Correlation between partial discharge (PD) activities and measured data in terms of phase resolved partial discharge (PRPD) patterns have been undertaken. The experimental results also show a decreasing trend of the average discharge magnitude during the formation of the white marks that propagate towards the earth bar. This finding is qualitatively comparable to on-line problems reported previously, i.e. there was a falling trend and no obvious evidence of imminent failure from the monitoring data of PD activity of a large power transformer that eventually suffered from an unexpected fault.